(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Since their clinical introduction more than 25 years ago, proton pump inhibitors (PPIs) have proven to be invaluable, safe, and effective treatments for a wide range of acid-related disorders. PPIs differ slightly in terms of their pharmacokinetic properties, metabolism, and FDA-approved clinical indications, despite the fact that all members of this class act in a similar manner by inhibiting active parietal cell acid secretion. Nonetheless, they all work well for managing peptic ulcer disease, whether it's simple or complicated, as well as gastroesophageal reflux disease. PPIs can cause breakthrough symptoms in some people, particularly at night, due to their short plasma half-lives and requirement for meal-associated dosing, despite their overall efficacy. To specifically address these limitations, longer-acting PPIs and technology to prolong conventional PPI activity have been developed, which may improve clinical outcomes.